Factors influencing alcohol consumption among university students in Southern Thailand - Phuwasin Buakate; Phiman Thirarattanasunthon; Paleeratana Wongrith (National Institute of Public Health - National Institute of Hygiene, 2022)
Background. Underage drinkers are the primary cause of death and illness worldwide. Initiation of drinking at younger ages and levels of drinking during young adulthood may also shape future public health by influencing alcohol consumption. From this situation, it is necessary to study various factors to provide sufficient information to reduce adolescent alcohol consumption. Objective. This study aimed to examine the prevalence and factors that influenced alcohol consumption of first-year students in a university network in Southern Thailand. Material and methods. A total participant 685 of 1,100 first-year students from 12 universities in southern Thailand were randomized and recruited using eligible criteria. The instrument was an online questionnaire based on the preceding model that consisted of 9 parts with 93 items. For descriptive analysis, percentages were used to describe the characteristics and alcohol consumption behaviours of participants. In addition, logistic regressions were used to determine the factors influencing. Results. The results showed 62.3% of participants responded to the online questionnaire. During the past six months, 36% reported consuming alcohol. Males reported drinking more (45.3%) than females. The most popular drink was beer (57.7%). There were 8.16 standard drinks, (82.3%) consumed at night, (70.2%) drank at their place, and consumed with friends (83.6%). The results of multiple logistic regression showed significant factors influencing drinking alcohol. The lower attitude was 2.56 times more likely to consume alcohol than a high level (AOR: 2.56, 95%CI: 1.53-4.28). Reversely, the higher marketing perception was more likely to consume alcohol than a low level (AOR: 5.35, 95%CI: 1.94-14.58). In addition, students with mother drinker, lover drinker, and close friend drinker were more likely to consume alcohol (AOR: 2.35, 95%CI: 1.07-5.16), (AOR: 3.60, 95%CI: 1.99-6.50), and (AOR: 5.29, 95%CI: 3.31-8.45) respectively. Conclusion. In conclusion, attitude, marketing factors, and social factors were associated with alcohol consumption among Thai university students that were revealed as positive predictors regarding binge drinking. The study shows how healthcare providers may reduce binge drinking by designing effective prevention programs.